PENEGAKAN KEADILAN HAKIKI DAN KETANGGUHAN KELUARGA, PEREMPUAN DAN ANAK DALAM PERSPEKTIF PARENTING GUS DUR - Jufri, Jumadi bin; Tarmizi, Tarmizi bin; Salman, Aulia Salman binti (IAIN BONE, 2024)
This study aimed to discuss the enforcement of essential justice and the resilience of family, women and children in Gus Dur's parenting perspective. The method used in this research is descriptive analytical with a qualitative approach and data collection techniques through literature studies and articles and the results of parenting seminars while the data analysis technique used content analysis. The results and discussion of this study provided a new breakthrough on the concept of a just, essential and resilient household life of women and children through the concept of literacy strengthening parenting, visionary parenting, theoretical and practical religious knowledge, the need for reading or books, development of resilience soft skills and education. honest character. This research is recommended for academics and institutions related to strengthening household justice and resilience so that they are disseminated or held in seminars to the public and become public policy on local government policies.